SYSTEMS OF COMPUTER-ORIENTED PROBLEMS IN THE COURSE OF DIFFERENTIAL EQUATIONS - Ilyasova, Р.А; Dauletkulova, А.У; Tokhtakhunov, Д.Я (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The modern period of development of the information society is characterized by the need to modernize the education system. The training of a future mathematics teacher should be organized in such a way that in addition to basic knowledge, future teachers should master various applications of mathematics, be able to model various processes and phenomena, and use modern information technologies in the process of solving mathematical problems. The use of computers and computer programs in the educational process changes the role of learning tools in teaching. In our study, we consider the computer as one of the components of the entire system of learning tools, which, in addition to the computer, includes traditional learning tools that ensure the teaching of an educational subject. This paper shows some advantages and disadvantages of computer mathematics systems in the course of differential equations. Computer programs that allow us to implement numerical, analytical and graphical methods for solving differential equations are considered.